(untitled) (Semiárida, 2024)
The use of saline water has adverse effects on crop productivity. The objective of this study was to quantify how plant cover (mulching) can modify the adverse effects of saline water on lettuce cultivation in two characteristic soils of the Pampas Semiarid Region. The statistical design was completely randomized a sandy soil and a sandy loam soil were analyzed. The treatments were with plant cover (CCV) and without it (SCV). Irrigation was carried out with water with an electrical conductivity of 1.0 (low salinity); 1.5 and 2.0 (high salinity) dS m-1. A dose of 100 kg N ha-1 was applied using a combination of urea and organic fertilizer (40:60). The lettuce crop was evaluated during four consecutive cycles during the years 2020 and 2021, with five repetitions in each cycle. Productivity was determined: total dry matter (MST), aboveground (MSA) and root (MSR). Accumulated MST (MSTAC), the MSA/MSR ratio, water use efficiency (EUA) and growth rate (TC) were calculated. Data from the fourth crop cycle are presented. The study confirms the negative effect of water with high salinity on MST in both soils, with significant losses in lettuce productivity. In the sandy soil with 1.0 dS m-1 water and CCV the yield was 1416 kg ha-1 with losses of 17 % compared to the treatments irrigated with 2.0 dS m-1 water, while SCV was 420 kg ha-1 with losses of 100 %. The effect of salinity and mulch on lettuce cultivation depends on soil texture, with the greatest effect on sandy loam soil. The use of residue cover improved EUA by 90 % in sandy soil and by 56 % in sandy loam soil.